Hydroxyl regulating effect on surface structure of BiOBr photocatalyst toward high-efficiency degradation performance. (January 2022) - Du, Cuiwei; Nie, Shiyu; Feng, Weiwei; Zhang, Jiale; Qi, Mingshuo; Liang, Yutong; Wu, Yuhan; Feng, Jinglan; Dong, Shuying; Liu, Haijin; Sun, Jianhui
Abstract: Herein, photocatalytic degradation of levofloxacin hydrochloride (LVF) by a simple surface hydroxyl strategy on BiOBr photocatalyst was studied under simulated visible light irradiation. Interestingly, the BiOBr contained abundant hydroxyl groups following its modification with glucose, which enhanced the photocatalytic degradation of levofloxacin hydrochloride (LVF). The degradation efficiency of LVF over the optimized composite of BiOBr-5 could reach 91.67% in 20 min, which was much higher than that of pristine BiOBr (59.26%). Following, the biotoxicity of antibiotics to Escherichia coli DH5a could be eliminated after LVF photocatalytic degradation. This strategy proposed in this work can provide new ideas for tuning the surface structures of photocatalysts via specific functional groups for the highly efficient degradation and efficient removal of antibiotics in wastewater. Graphical abstract: Image 1 Highlights: A simple hydroxyl-regulated strategy was harnessed to modify a BiOBr photocatalyst. Hydroxyl-rich BiOBr materials exhibited enhanced photocatalytic degradation performance. The roles of hydroxyl radicals were identified during the photocatalytic process. Potential mechanism and transformation pathways for the photocatalytic degradation of LVF were proposed.